Editorial policy of Economic Notes—1993–1998. (1st February 2023) - Vercelli, Alessandro
Abstract: The context had radically changed when Economic Notes entered its third decade of activity. Specifically, the 1990s seemed to carry along a wave of conformity and of endangered pluralism in economic thought behind the mounting neoliberal economics mainstream. This paper reviews how the task of preserving pluralism in economic thought was resolutely pursued at Monte dei Paschi's publishing venture by placing the Journal on impartial grounds and keeping the door open to diversity.